DELINIATION OF SHALLOW GAS ZONE POTENTIAL USING SUBSURFACE DATA APPROACH IN ‘X’ FIELD KUTAI BASIN - Yuniardi, Yuyun; Alfadli, Muhammad Kuniawan; Mohammad, Febriwan; Natasia, Nanda; Nur, Andi Agus (Fakultas Teknik Geologi Universitas Padjadjaran, 2025)
The presence of shallow gas (Shallow Gas) in exploration wells poses significant operational risks, including kicks or blowouts during exploration activities. To mitigate these risks, it is essential to delineate subsurface data and identify areas potentially containing shallow gas. Subsurface interpretation was conducted using various datasets, including electrolysis cutting analysis, well log data (GR, RT, NEU, RHOB) from 39 wells, and gas data obtained from chromatograph-based mud logs. Well correlation was performed to identify anomalies, gas presence, and facies characteristics.The primary stratigraphic marker surfaces indicative of shallow intervals in Field X are, from deeper to shallower, MF2, Fs-s1, s2-Fs, Fs-s3, Fs-s4, Fs-s5, and Fs-s6, with the shallow gas accumulation predominantly observed within the intervals associated with Fs-s2 and Fs-s3, at depths ranging from approximately 950 to 1300 meters below sea level (MSS). These intervals demonstrate isolated gas accumulations, primarily comprising methane (C1), with minor traces of C2, C3, C4, and C5 gases detected in the shallow zone above the marker MF2.Gas analysis indicates a surge in total gas content within the 950-1300 MSS interval, correlating with anomalies identified from the Master Log data. This surge is attributed to limestone and coal layers, as corroborated by gas bearing reservoir mapping.Based on the analyzed data, it can be concluded that shallow gas accumulations are localized within the 950-1300 MSS interval, specifically between the Fs-s2 and Fs-s3 markers. For subsequent drilling activities on Platform M, it is recommended to monitor and consider this depth zone to mitigate related risks effectively.